THE FACTORS OPPOSING THE IMPLEMENTATION OF INNOVATIVE AND INVESTMENT PROJECTS IN THE INDUSTRY - V. Mylnik; A. Mylnik; E. Zubeeva (Вестник университета)
This article aims to identify the key external factors, which impede the realization of innovation and investment projects in industrial enterprises in contemporary Russia and to propose measures to address them. As the main factors weak patent protection, the absence of experimental base, MIP, poorly developed strategies and barriers to innovation risks insurance.